A study of yield, its components and their relationship to some morphological and physiological indicators of Lathyrus sativus. L under the influence of salt stress - ضاهر, ميس; صالح قبيلي,; سوسن هيفا , (Latakia University Journal -Biological Sciences Series, 2023)
The experiment was carried out in the greenhouse of the Faculty of Agricultural Engineering - Tishreen University - Latakia during the agricultural season 2021-2022 by planting seeds of four genotypes of Lathyrus sativus L. (Latakani, Tartous, Homs, and Shami) in plastic bags with a capacity of 5 kg of soil consisting of ( 1:1:2) (soil: organic matter: sand), which was distributed according to a randomized complete design (RCD) at a rate of three replicates for each treatment. The research aimed to evaluate the behavior of some morphological and physiological characteristics of the studied guinea pigs under different levels of salinity of irrigation water with sodium chloride (0, 3, 6, 10 and 15 mm/cm) in order to determine the most effective salinity levels and the most tolerant genotype for future use in breeding programs or... Cultivation in lands affected by salinity. Salt concentrations, especially at high levels (10 and 15) mmM/cm, negatively affected the growth of the studied models compared to the control and other treatments, which led to a deterioration in most of the studied traits, especially yield and its components. The Lathakani type was superior in terms of plant height (cm) compared to the rest of the other models and the control, while the Homsi type achieved the highest density of vegetative growth and the highest productivity compared to the rest of the other models and the control. Accordingly, low concentration salinity levels (3 and 6 mm/cm) can be used to irrigate grasses.